The State of Food and Agriculture 2019 - Food; Agriculture Organization of the United Nations (United Nations, 2019)
This year's edition provides new estimates of the percentage of the world's food lost from production up to the retail level. It suggests that identifying and understanding critical loss points in specific supply chains – where considerable potential exists for reducing food losses – is crucial to deciding on appropriate measures. It also provides some guiding principles for interventions based on the objectives being pursued through food loss and waste reductions, be they in improved economic efficiency, food security and nutrition, or environmental sustainability.